Experience in implementing the European Union’s regional investment policy to attract foreign direct investments - L. S. Nevyantseva; N. Yu. Vlasova (Управление)
The article reviews the investment policy of the Eurozone regions in relation to foreign direct investments (hereinafter-FDI). A quantitative assessment of FDI in the global aspect and at the level of the European Union has been given. It has been determined that both global FDI flows and at the level of the EU economy decreased at the end of 2018. The rating of the Eurozone countries by the level of FDI for 2018, the leaders of which are Germany, Ireland and France, is given. The FDI market by type of economic activity has been analysed. It has been revealed that a large share of the market is made up of sales and marketing (up to 40%) and production sector (up to 30%). In more detail the trends in the investment policy of those countries that recorded a sharp growth or a sharp decline in FDI have been highlighted, namely, France, Germany, Spain, Belgium, Poland and Ireland. The main factors that negatively affect the investment situation in the European Union have been emphasized, including: General political instability, threats of global protectionism, high levels of public debt in a number of countries, fiscal reform and US economic policy, and others.At the end, taking into account the current problems in the EU, recommendations have been formulated to activate the investment policy in the field of FDI at the level of this regional Association, aimed at promoting its socio-economic development. The main focus of investment policy development in the EU countries should be on aspects that promote macroeconomic and political stability, create a favorable business environment and create a reliable legal framework. In addition, it is extremely important to carry out structural reforms in the financial sector: to reduce the budget deficit and public debt in a number of countries. In conclusion, it is emphasized that by implementing an investment policy in accordance with the current needs of the Eurozone economy, it is possible to reduce the gap in the development of European regions and create an integrative and stronger economic Union.